PERANCANGAN JIG MAIN STEAM DI PT. TOMOE VALVE BATAM - simanjorang, aron futra; Arista, Anggia (Computer Science and Industrial Engineering, 2020)
Tomoe Valve Batam is a Manufacturing of Butterfly Valve, Accuator and Accessories. manufacture. PT. Tomoe Valve Batam has difficulty in fulfilling order orders because the Main Steam product setting process is too long so the production capacity is low, so it is necessary to design a Jig in the Main Steam product setting process in order to eliminate the processing time setting. This research was conducted at the production division using the Quality Function Deployment analysis method. The stages in this study use Voice of Costumer which is useful to find out the company's interests, product attributes and technical responses in order to eliminate the long set up time so that production capacity is reached. After that stage is completed, an analysis is conducted using the QFD method. Identify the quality deployment function (QFD) as one of the tools that can be used to identify customer needs and link the needs to product design. PT. Tomoe Valve Batam was success to cut off settiing time with QFD method to increasing production output.